2005
DOI: 10.1055/s-2005-871525
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis in a Premature infant as the Presenting Symptom of Familial Dysautonomia in the Neonatal Period: Case Report and Review of the Literature

Abstract: We present a case of a premature infant with early-onset necrotizing enterocolitis as the presenting symptom of familial dysautonomia. The diagnosis of familial dysautonomia in the neonatal period is usually rare and difficult, because many of the symptoms may be mild or nonspecific, whereas other characteristic signs and symptoms appear only later in life. The neonatologist should be aware of this rare diagnosis in the neonatal period, especially in the offspring of Ashkenazi Jews. The diagnosis is genetic. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…48 As in the general population, the incidence of necrotizing enterocolitis in FD patients is more common in low birth weight, premature babies. 49 Two cases of intestinal ischemic necrosis in older FD children have been reported.…”
Section: Gastrointestinal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 As in the general population, the incidence of necrotizing enterocolitis in FD patients is more common in low birth weight, premature babies. 49 Two cases of intestinal ischemic necrosis in older FD children have been reported.…”
Section: Gastrointestinal Treatmentsmentioning
confidence: 99%
“…Its causes in FD are unknown. 48, 52 Management requires intensive supportive care with the administration of intravenous fluids and pressor agents. Anti-cytokine agents and corticosteroids may be used to suppress inflammation.…”
Section: Gastrointestinal Treatmentsmentioning
confidence: 99%
“…NEC most frequently occurs in premature and sick infants, with an incidence of 1.5-7.2%, and its development is influenced by many different factors (1). It has been demonstrated that ischemic hypoxia leads to localized necrosis or necrosis of the entire intestine and colon (2).…”
Section: Introductionmentioning
confidence: 99%